From Self-Love to Self-Growth: Empowering Students to Recognize Their Potential at Witthayapanya Matthayom School, Thailand - Hasmalawati, Nur; Vonna, Rizka Dara; Khafidhoh, Khafidhoh; Isni, Khoiriyah; Selian, Sri Nurhayati; Yanti, Devi; Amalia, Hanna; Farika, Siti; Azra, Shafiana; Mutia, Cut Risa; et al. (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance students’ self-awareness and personal development through self-love and self-growth approaches at Witthayapanya Matthayom School, Thailand. The program encourages students to recognize the importance of self-acceptance by identifying their strengths and weaknesses and developing a positive self-concept as a foundation for personal and career development. Students are also guided to foster self-growth through goal setting, self-improvement motivation, and the ability to realistically accept the process of personal change. The program is implemented through the delivery of educational materials and the application of Cognitive Restructuring (CR) techniques within a Cognitive Behavioral Therapy (CBT) framework. Program effectiveness is evaluated using a 10-item questionnaire measuring self-concept, self-love, and self-growth, administered on a 4-point Likert scale and developed through an Item Response Theory (IRT)–based adaptation of the Rosenberg Self-Esteem Scale (RSES). Descriptive statistical analyses, including frequencies, percentages, and means, are used to summarize students’ responses and are complemented by qualitative observations from discussions and reflective activities. The results indicate high levels of student engagement, as evidenced by enthusiasm, active participation, and experience sharing throughout the sessions. These positive responses reflect increased awareness of self-love, contributing to enhanced self-confidence, motivation, and engagement in positive daily activities. Furthermore, the program strengthens students’ self-growth, as demonstrated by increased motivation for self-improvement, clearer future-oriented goals, and a stronger commitment to becoming the best version of themselves. Overall, this education- and CBT-based program is empirically relevant to students’ developmental needs, strengthens self-concept, and supports sustainable personal development for future readiness.